2022
DOI: 10.3390/diagnostics12020480
|View full text |Cite
|
Sign up to set email alerts
|

Vedolizumab Attenuates Immune-Checkpoint-Therapy-Induced Infliximab-Refractory Colitis

Abstract: Immune checkpoint inhibitors (ICIs), such as nivolumab and ipilimumab, have drastically changed treatments of advanced melanoma. However, ICI-related enterocolitis is often the most common adverse event, and represents the main reason for ICI discontinuation and mortalities. Here, we report the case of a metastatic melanoma treated with vedolizumab for ICI-induced colitis. A 67-year-old man treated with ipilimumab and nivolumab developed ICI-induced colitis and grade 3 diarrhea refractory to methylprednisolone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…[ 10 ] In addition, the NCCN (National Comprehensive Cancer Network) guidelines also mention that vedolizumab may be considered if infliximab is ineffective or contraindicated. [ 11 , 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] In addition, the NCCN (National Comprehensive Cancer Network) guidelines also mention that vedolizumab may be considered if infliximab is ineffective or contraindicated. [ 11 , 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…As far as recurrence of colitis, the vedolizumab group also had lower rates compared with the infliximab group. Important to note, vedolizumab is a gut-specific agent and is not known to help treat any other nongastrointestinal-related irAEs [28 ▪▪ ,29].…”
Section: Treatmentmentioning
confidence: 99%
“…7 In previously published cases, the benefit of vedolizumab in patients with severe immune-mediated colitis has been reported. 8,9 Our case highlights that vedolizumab could be used to minimize the risk of recurrent immunotherapy-related colitis. A study with 14 patients reported similar results: The use of vedolizumab in patients with previous immunotherapyrelated colitis after CPI lowered the rate of recurrent colitis in this small cohort (12% vs. 50%).…”
mentioning
confidence: 91%